Implikasi dan Implementasi Putusan Mahkamah Konstitusi Nomor 5/Puu-X/2012 tentang SbI atau RSbI - Fajar Laksono; Winda Wijayanti; Anna Triningsih; Nuzul Qur’aini Mardiya (Jurnal Konstitusi, 2016)
Constitutional Court Decision No. 5/PUU-X/2012 is very important and interesting to be studied because due to its implications and implementation. Ministry of Education and Culture as the addressat of the decision make transitional policy regarding on how to eliminate the policy concenring International Standard School/ International-Standard School Pilot Project (SBI/RSBI). In fact, transitional policy  is not addressed and does not have a legal basis in the implementation of the decision. There is a conflict between the normative provisions that Constitutional Court Decision are binding since   pronounced in an open session for the public   with the certainty of  cross-state agency collaborative cooperation to implement  the Court Decision. Therefore, there’s a need to investigate this Decision at the practical leve on how the decision is implemented. This research is doctrinal in which the object of the research is laws and regulations and other legal materials, in this case, the Constitutional Court Decision No. 5/PUU-X/2012. In addition, field studies are also conducted by way of searching mass media news which is important to be done in order to know the response of the public on how to implement the Constitutional Court Decision No. 5/PUU-X/2012.  The  results  showed  that  (1)  the implications of the Constitutional Court Decision No. 5/PUU-X/2012 is that it eliminates the legal basis of RSBI policy. Consequently , the implementation of SBI/ RSBI should be stopped because it has lost its legal basis since the judgment is pronounced. In addition, the Government through the Ministry of Education and Culture, shall implement the decision, including to repeal or revise the technical regulations that become legal framework of RSBI, (2) The implementation of the Constitutional Court Decision No. 5/PUU-X/2012 can be seen in two categories, namely: (a) spontaneous implementation, which is implementation by some education authorities and the schools themselves by removing the attributes of SBI/RSBI shortly after the Constitutional Court’s decision was pronounced, without waiting for further instruction by Ministry of Education and Culture, and (b) a structured implementation through the Ministry of Education and Culture by issuing Circular of Minister of Education and Culture No. 017/MPK/SE/2013 about RSBI Transition Policy. Although this policy is contrary to normative-imperative provisions, the measure taken by the Ministry of Education and Culture to establish a transition policy is the most probable step taken in order that the Constitutional Court Decision No. 5/PUU-X/2012 can be implemented as it should be.